2000
DOI: 10.1099/00221287-146-6-1321
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel gene, fimV, involved in twitching motility in Pseudomonas aeruginosa The GenBank accession number for the sequence determined in this work is U93274.

Abstract: Transposon mutagenesis was used to identify a new locus required for twitching motility in Pseudomonas aeruginosa. Four Tn5-B21 mutants which lacked twitching motility and a fifth which exhibited impaired motility were found to map to the same KpnI restriction fragment at approximately 40 min on the P. aeruginosa genome. Cloning and sequencing studies showed that all five transposon insertions occurred within the same 28 kb ORF, which was termed fimV. The product of this gene has a putative peptidoglycan-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 60 publications
3
66
0
Order By: Relevance
“…The fimV mutant grew as well as wild-type PAK in L broth with (type III inducing condition) or without 5 mM EGTA. As reported by Semmler et al (2000), the fimV mutant was completely defective in twitching motility (Fig. 1), although type IV pili were observed on the surface by scanning electron microscopy.…”
Section: Identification Of P Aeruginosa Mutants Defective In Hela Cementioning
confidence: 61%
See 1 more Smart Citation
“…The fimV mutant grew as well as wild-type PAK in L broth with (type III inducing condition) or without 5 mM EGTA. As reported by Semmler et al (2000), the fimV mutant was completely defective in twitching motility (Fig. 1), although type IV pili were observed on the surface by scanning electron microscopy.…”
Section: Identification Of P Aeruginosa Mutants Defective In Hela Cementioning
confidence: 61%
“…cyaA encodes a protein that shares 54 % similarity with adenylate cyclase of E. coli (Aiba et al, 1983) and was recently reported to be essential for efficient expression of the type III genes in response to the low-calcium signal (Wolfgang et al, 2003); thus its effect on cell lifting is understandable. FimV is a twitching motility protein (Semmler et al, 2000) and PilL is a probable component of the chemotactic signal transduction system, with its C-terminal half showing 51 % similarity to chemotaxis protein CheA of Synechocystis sp. (Mattick et al, 1996); thus twitching motility might affect the type III secretion as previously suggested (Comolli et al, 1999, Kang et al, 1997.…”
Section: Identification Of P Aeruginosa Mutants Defective In Hela Cementioning
confidence: 99%
“…uk) which is thought to have a general peptidoglycan binding function and to be present in a variety of enzymes involved in bacterial cell degradation (Interpro entry IPR018392). As FimV has been shown to be involved in type IV pilus assembly (Semmler et al, 2000), one could imagine that the loss of FimV affects a peptidoglycan breaching step necessary for pilus assembly. It could also be possible that the same peptidoglycan breaching mechanism is required for assembly of the T2SS machinery.…”
Section: Influence Of Fimv On Lasb Expressionmentioning
confidence: 99%
“…The former gene encodes a well-known global regulator that controls several processes (expression of genes encoding proteases, exotoxin A, twitching motility and QS) (Albus et al, 1997;Beatson et al, 2002;Suh et al, 2002;Kanack et al, 2006;Fox et al, 2008) and the latter encodes a protein involved in type IV pili assembly but has been poorly studied so far (Semmler et al, 2000;Ahn et al, 2004). Both genes were also reported to be required for twitching motility and indeed, as expected, we observed that the selected mutants were impaired for this movement mode (data not shown).…”
Section: Genes Involved In the Regulation Of Expression Of The Paqa Omentioning
confidence: 99%
“…141 These 'rafts' or 'trails' of cells move radially outwards, always in cell-to-cell contact, leading to a dynamic lattice-like network (Figure 4). 141,144 Biofilm formation ensues once a mature lattice with less motile cells and a higher three dimensionality begins to develop.…”
Section: Swimming Motilitymentioning
confidence: 99%